Free Anterolateral Thigh Flap in the Repair of Bronchial Stump Blow-outs - Nadia Hui Shan Sim; Yang Chong Chua; Wei Hao Liang; Agasthian Thirugnanam; Chong Hee Lim; Bien-Keem Tan (Journal of Plastic and Reconstructive Surgery, 2023)
A bronchial stump blow-out is a serious complication following pneumonectomy/lobectomy. A blown-out stump requires well-vascularized tissue for healing and successful closure. We illustrate the use of the free anterolateral thigh flap in two patients. For patient 1, a chimeric anterolateral thigh flap was used to seal the bronchial stump following an upper lobectomy for tuberculous bronchiectasis. For patient 2, an anterolateral thigh flap was used to seal the main bronchial stump that had blown-out following pneumonectomy for actinomyces lung abscess. The latissimus dorsi muscle was unavailable in both cases due to a previous thoracotomy. Patient 1 had a persistent bronchial leak post-operatively, which resolved after anti-tuberculous treatment. Patient 2 recovered uneventfully and was discharged 14-days post-operatively. Their follow-ups were 13 years and 4 months respectively. In conclusion, the free anterolateral thigh flap is an alternative option to seal a blown-out bronchial stump in the absence of the latissimus dorsi muscle flap.